Evidence of Tectonic Control on the Geochemical Features of the Volatiles Vented along the Nebrodi-Peloritani Mts (Southern Apennine Chain, Italy). (4th July 2019) - Italiano, Francesco; Bonfanti, Pietro; Maugeri, Salvatore Roberto
Abstract : Investigations carried out over the southernmost portion of the Apennine chain (Nebrodi-Peloritani Mountains, Sicily, Italy) reveal a close connection between the tectonic setting and the regional degassing of CO2 -dominated volatiles. The geochemical features of the collected gases show that the pristine composition has been modified by gas-water interaction (GWI) and degassing processes. The 3 He/ 4 He isotopic ratio in the range of 0.7-2.8 Ra highlights variable contributions of mantle-derived helium, representing an unusual feature for the crustal regime of the study areas characterized by the widespread presence of 4 He-producer metamorphic rocks. The degassing of mantle helium is coherent with the tectonics and related to the NW-SE extensional regime of the Calabro-Peloritan Arc (CPA). We propose that the degassing regime as well as the geochemical features of both the dissolved and bubbling gases is closely connected to the strain accumulation rate, inducing almost no temporal changes and insignificant deep-originated fluid contributions to the locked fault volumes. Investigations including discrete and continuous monitoring and degassing-rate estimations are useful tools to gain a better insight into the evolution of seismogenesis, considering the fault rupture as the final stage of a seismic cycle.